C-reactive protein (crp) as a supporting marker of antibiotic effectiveness on central nervous system (cns) infections - Olevianingrum, Melawati; Yulistiani, Yulistiani; Saharso, Darto; Zairina, Nun (Folia Medica Indonesiana, 2016)
Infection of the central nervous system in pediatric patients have a high mortality as well as acute and chronic neurological sequelae. Signs of the disease are unclear, so cerebrospinal fluid (CSF) test is used as a gold standard for diagnosis, but the investigation has faced many obtacles. Empiric antibiotic therapy is the key factor in reducing morbidity and mortality. Microbiological culture result is obtained within 5-7 days. The effectiveness of empirical antibiotic use is questionable. Therefore, other investigations are conducted to determine the effectiveness of antibiotics by using one marker, the CRP. This study was to analyze CRP level in supporting antibiotic therapy effectiveness in pediatric patients with central nervous system (CNS) infections. A prospective cohort study was conducted to determine the relationship of CRP with other parameters, including clinical, microbiological and laboratory, in pediatric patients with central nervous system infections. Patients meeting blood samples criteria were taken before (H0), the third day (H3) and the fifth day (H5) after antibiotics administration. This study involved 10 patients with central nervous system infections (meningoencephalitis, encephalitis and encephalitis with cerebral edema). Six patients were male, with ages less than a year. Antibiotic treatment effectiveness was associated with improved condition of the patients' CRP level. It was 3.558 ±3.196 before (H0), 3.878±2.813 on the third day (H3) and 3.891±2.204 on the fifth day (H5) after antibiotic administration. Leukocyte levels were 13.680±1.660 before (H0), 17.832±7.213 on the third day (H5), and 10.546±3.671 on the fifth day (H5) after antibiotic administration. Pearson's correlation test analysis performed on CRP and WBC parameters showed H0 p=0.981, CRP and WBC H3 p=0.621, while CRP and WBC H5 obtained significance p=0.644. There was no significant correlation observed between CRP and WBC parameters before and after antibiotic administration. In conclusion, there was no correlation of CRP levels with clinical, laboratory and micobiological parameters in patients with central nervous system infections.